Determinant factors of FDI spillovers - What do we really know? - Crespo, N. (2021)
The evaluation of aggregate FDI spillovers to domestic firms has yielded mixed results. However, analysis has recently taken a step forward with the evaluation of the factors determining the existence, dimension, and sign of FDI spillovers. We survey the arguments that support these factors and the empirical evidence already produced. FDI spillovers depend on many factors, frequently with an undetermined effect. The absorptive capacities of domestic firms and regions are preconditions for incorporating the benefits of these FDI externalities. Regarding the remaining factors, the results show contrary effects or, in some cases, are still insufficient to draw reliable conclusions.